2018
DOI: 10.1002/slct.201800138
|View full text |Cite
|
Sign up to set email alerts
|

Natural Acidic Ionic Liquid Immobilized on Magnetic Silica: Preparation and Catalytic Performance in Chemoselective Synthesis of Dicoumarols and Substituted Xanthene Derivatives

Abstract: A novel magnetically separable natural acidic ionic liquid immobilized on magnetic silica were fabricated by covalent bonding of thiamine (VB1) modified with (3‐glycidyloxypropyl)trimethoxysilane (GMSI) moiety on the silica modified Fe3O4. The catalytic properties have been evaluated in one‐pot multi‐component synthesis of biscoumarins and substituted xanthene derivatives through the Domino Knoevenagel‐Michael reaction of a wide range of substrates under solvent free conditions. A variety of readily accessible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…As a part of ongoing research into the efficient synthesis of heterocyclic compounds [32][33][34][35][36], in the present study, we describe a green and effective procedure for the Nalkylation of aromatic amines with alcohols using H At first, the reaction of aniline (1 mmol) and benzhydrol (1 mmol) in the presence of 0.05 g of the catalyst in various solvents at 60 o C was selected as a model reaction ( Table 1). The results indicated that, among all, C 2 H 5 OH/H 2 O (1:1) is the most effective solvent.…”
Section: Resultsmentioning
confidence: 99%
“…As a part of ongoing research into the efficient synthesis of heterocyclic compounds [32][33][34][35][36], in the present study, we describe a green and effective procedure for the Nalkylation of aromatic amines with alcohols using H At first, the reaction of aniline (1 mmol) and benzhydrol (1 mmol) in the presence of 0.05 g of the catalyst in various solvents at 60 o C was selected as a model reaction ( Table 1). The results indicated that, among all, C 2 H 5 OH/H 2 O (1:1) is the most effective solvent.…”
Section: Resultsmentioning
confidence: 99%
“…A novel, one‐pot and potent pathway to synthesize biscoumarins from aldehydes and 4HC via domino Knoevenagel–Michael reaction using tetramethylguanidium‐acetate [TMG][Ac] as an ionic liquid catalyst at room temperature has been presented by Zhu and colleagues ( Scheme : Method 6) . Azizi and co‐authors prepared a catalyst by natural acidic IL immobilized on magnetic silica (Fe 3 O 4 @SiO 2 @VB1‐Ni II ) and used this catalyst in protocol to form biscoumarin from 4HC and aldehyde in solvent free condition at 110 °C ( Scheme : Method 7) .…”
Section: General Synthesis Of Biscoumarinmentioning
confidence: 99%
“…Xanthene and its derivatives are the most promising biologically active compounds with great pharmaceutical applicability [2][3][4][5][6]. Furthermore, these compounds have been utilized in local dyes [7], laser technologies [8,9], and photodynamic therapy [10]. Structures of some bioactive xanthenes (rhodamine, amsacrine, and RO67-4853) [11] are depicted in Figure 1.…”
Section: Introductionmentioning
confidence: 99%